Differential expression of 3Î²-HSD and mlncRNAs in response to abiotic stresses in Digitalis nervosa - Salimi, Vahideh; Maroufi, Asad; Majdi, Mohammad (Cellular and Molecular Biology, 2018)
Digitalis nervosa is an important medicinal plant species belonging to the family of Scrophulariaceae that has the potential to be used for heart failure. 3Î²-hydroxysteroid dehydrogenase (3Î²-HSD) is a key gene in the biosynthesis of cardenolides for making digitalis effective compounds, hence identification of this gene is important for genetic engineering purposes towards increasing the yield of cardiac glycosides. In addition, mRNA-like non-coding RNAs (mlncRNAs), a class of long non coding RNAs, play key roles in various biological processes and may affect cardenolides pathway in digitalis plants. In the present work, full sequence of 3Î²-HSD was isolated from Digitalis nervosa. Gene expression patterns of 3Î²-HSD along with three mlncRNAs including mlncRNA23, mlncRNA28 and mlncRNA30 were studied and the results indicated that they are differentially expressed in different tissues including roots, stems and leaves, with the highest expression levels in leaves. Moreover, the transcript levels of these genes affected by the cold and drought stresses. The results obtained from the present study is important in order to understand the potential role of mlncRNAs in digitalis plants, especially in response to abiotic stresses.